Manajemen Komunikasi Proyek pada Proyek Infrastruktur Teknologi Informasi - Azhari, Ozmar (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The implementation of Information Technology (IT) infrastructure projects frequently experiences failures—such as schedule delays, cost escalation, and stakeholder rejection of deliverables, because of ineffective communication between vendors and internal stakeholders. This study evaluates how far optimizing communication planning, information distribution, performance reporting, and documentation processes can improve project communication effectiveness and reduce conflict. A qualitative case study was carried out on an IT infrastructure project at a national telecommunications company through field observation; analysis of project documents, such as communication plans, weekly reports, and meeting minutes; and structured interviews with the project manager, vendor team, and internal departments, such as planning, project management, and regional operations. Coordination patterns were identified to verify the consistency and reliability of data sources. Findings indicate that a combination of routine face‑to‑face meetings, periodic reporting, and the use of digital collaboration platforms, such as a project portal, Jira, and Microsoft Sharepoint, Teams, accelerates issue detection and expedites technical decision‑making compared with previous project cycles. Disciplined communication documentation also reduces conflict and administrative disputes by providing clear mitigation evidence, including comprehensive project records and well‑defined escalation paths when scope changes occur. An integrated set of communication procedures across all departments enhances transparency, aligns stakeholder expectations, and lowers the risk of failure, particularly in IT infrastructure projects.